A five-year strategic financial plan for Philippine Diamond Hotel & Resort, Inc. - Arevalo, Allen Carlos O., Canatoy, Angel I., Collantes, Lea Denise D., Navarro, Isaiah Daniel Michael M., Olaes, Renz Anne A., Olat, Danica Rose S., Peji, Rhona Joie M., Tabien, Marion C. 4 0 16; 5
EXECUTIVE SUMMARY The Philippine Diamond Hotel & Resort, Inc. a 5-star hotel minutes from the airport, convention centers, cultural institutions, historical monuments, and retail locations, is located against the overlooking scenic Manila Bay. The hotel has a number of restaurants and bars that specialize in various cuisines, providing guests with a variety of dining options. This report analyzes the financial operations and performance of the entity for five years. This will provide an assessment and analysis of the profitability, liquidity, solvency, efficiency, and leverage among other financial performances of Philippine Diamond Hotel & Resort, Inc., using the figures from the audited financial statements of the entity from the year 2017 to 2021. In the analysis, financial ratios were used to have an imperative review of the specific areas of assessment of the company's performance. The ratios were able to provide a clear view of the overall performance of the company. Following an in-depth examination of the facts and data gathered on Philippine Diamond Hotel & Resort, Inc., as well as a thorough interpretation of their financial statements, the proponents recommend the first and second alternative courses of action: Achieving market penetration through digital marketing and Improvement of claims and collection of receivables. The proponents recommend improving the entity's digital marketing presence to attract more customers and exposure to help them increase revenue. The second ACA is implemented to increase the receivables collection of the entity.
Financial Plan: (BSBA major in Financial Management) - Pamantasan ng Lungsod ng Maynila, 2022
Keywords: 2 -- 0; 6; 20; 20; 2